Humanized cereblon mice revealed two distinct therapeutic pathways of immunomodulatory drugs - Gemechu, Yohannes (Proc Natl Acad Sci U S A, 2018)
Immunomodulatory drugs (IMiDs), including thalidomide derivatives such as lenalidomide and pomalidomide, offer therapeutic benefit in several hematopoietic malignancies and autoimmune/inflammatory diseases. However, it is difficult to study the IMiD mechanism of action in murine disease models because murine cereblon (CRBN), the substrate receptor for IMiD action, is resistant to some of IMiDs therapeutic effects. To overcome this difficulty, we generated humanized cereblon (CRBN(I391V)) mice thereby providing an animal model to unravel complex mechanisms of action in a murine physiological setup. In our current study, we investigated the degradative effect toward IKZF1 and CK-1α, a target substrate of IMiDs. Unlike WT mice which were resistant to lenalidomide and pomalidomide, T lymphocytes from CRBN(I391V) mice responded with a higher degree of IKZF1 and CK-1α protein degradation. Furthermore, IMiDs resulted in an increase in IL-2 among CRBN(I391V) mice but not in the WT group. We have also tested a thalidomide derivative, FPFT-2216, which showed an inhibitory effect toward IKZF1 protein level. As opposed to pomalidomide, FPFT-2216 and lenalidomide degrades CK-1α. Additionally, we assessed the potential therapeutic effects of IMiDs in dextran sodium sulfate (DSS)-induced colitis. In both WT and humanized mice, lenalidomide showed a significant therapeutic effect in the DSS model of colitis, while the effect of pomalidomide was less pronounced. Thus, while IMiDs’ degradative effect on IKZF1 and CK-1α, and up-regulation of IL-2, is dependent on CRBN, the therapeutic benefit of IMiDs in a mouse model of inflammatory bowel disease occurs through a CRBN–IMiD binding region independent pathway.